Health on equal terms? - Västra Götaland, 2011 - Health on equal terms, Västra Götaland: National questionnaire - 2011 - Public Health Agency of Sweden (Region Västra Götaland, 2015)
The survey “Health on equal terms?” is a national survey, conducted every year since 2004.
The Public Health Agency is responsible for the survey and Statistics Sweden (SCB) is responsible for the distribution, collection and registration. During the data collection in 2011, Region Västra Götaland ordered an additional sample for Västra Götaland County. The sample was divided in two different parts of which 20 % received the national questionnaire and 80 % received a variant of the questionnaire (called the test questionnaire).

The additional sample in 2011 included all individuals aged 16-84 years living in Västra Götaland County. A total of 51,979 individuals answered the national questionnaire and the test questionnaire, representing a response rate of 54 percent.

Region Västra Götaland wanted to create a longitudinal cohort for further follow-ups, and 40,000 of the sample were invited to participate.

The questionnaire was printed in two versions: the national questionnaire included a total of 142 questions and the test questionnaire included a total of 127 questions. Both questionnaires covered issues of health, lifestyle, economic conditions, work and employment, and security and social relations. In addition to data collected through the questionnaires, registry data were also included.

Purpose:

The aim of the national survey was to investigate the health in the population and to show changes in the population's health over time as a follow up of the national health politics. The aim of the additional sample in Västra Götaland County was to investigate the health in the population in Västra Götaland County.

Undersökningen ”Hälsa på lika villkor?” är en stor nationell undersökning som genomförts varje år sedan 2004. Folkhälsomyndigheten ansvarar för undersökningen medan Statistiska centralbyrån (SCB) ansvarar för utskick, insamling och registrering av svar. I samband med undersökningen 2011 beställde Västra Götalandsregionen ett tilläggsurval för Västra Götalands län. Västra Götaland delade upp sitt tilläggsurval i två olika delar varav 20 % fick den nationella blanketten och 80 % en egen variant (kallad för testblankett).

Tilläggsurvalen inkluderade samtliga invånare 16-84 år i Västra Götalands län.

Det totala antalet svarande, från den nationella frågeblanketten och testblanketten, var 51 979 individer vilket motsvarade ca 54 % av urvalet.

Västra Götalandsregionen ville även skapa en framtida kohort för återkommande undersökningar och 40 000 individer av det totala urvalet fick förfrågan om de godtog en sådan medverkan.

Det trycktes två olika versioner av frågeblanketten, dels den nationella frågeblanketten och dels en specialblankett (testblankett) som innehöll vissa gemensamma frågor med den nationella blanketten. Den nationella frågeblanketten bestod av 84 numrerade frågor varav flera hade delfrågor, vilket genererade totalt 142 frågor. Testblanketten bestod av 75 numrerade frågor varav flera hade delfrågor, vilket genererade totalt 127 frågor. I båda blanketterna fanns frågor om hälsa, levnadsvanor, ekonomiska förhållanden, arbete och sysselsättning samt trygghet och sociala relationer. Därtill fanns även ett antal registervariabler som hämtats från SCB:s Registret över totalbefolkningen (RTB), utbildningsregistret och inkomst- och taxeringsregistret samt Geodatabasen.

Syfte:

Syftet med den nationella undersökningen var att ta reda på hur Sveriges befolkning mår och lever och även att följa upp den nya folkhälsopolitiken. Syftet med urvalet för Västra Götalands län var att ta reda på hur befolkningen i Västra Götalands län mår och lever.

Av tilläggsurvalet fick 20 % den nationella blanketten. Totalt var det 10 190 personer som besvarade den nationella blanketten, vilket motsvarade 53,3 % av urvalet.
Hälsa på lika villkor? - Västra Götaland, 2011 - Hälsa på lika villkor, Västra Götaland: Nationell blankett - 2011
Keywords: Health Services; Hälso- och sjukvård; Physical Examination; Hälsokontroll; Dental Care; Tandvård; Hearing; Hörsel; Life Style; Livsstil; Medicine; Medicin; Exercise; Träning; Population Surveillance; Populationsövervakning; Hearing Loss; Hörselnedsättning; Socioeconomic Factors; Socioekonomiska faktorer; Tinnitus; Öronsusning; Urinary Incontinence; Urininkontinens; Anxiety; Ångest; Overweight; Övervikt; Diet; Kost; Alcohol Drinking; Alkoholkonsumtion; Work; Arbete; Asthma; Astma; Diabetes Mellitus; Diabetes; Eczema; Eksem; Public Health; Folkhälsa; Leisure Activities; Fritidsaktiviteter; Cardiovascular Diseases; Kardiovaskulära sjukdomar; Headache; Huvudvärk; Health; Hälsa; Health Status; Hälsotillstånd; Hypertension; Högt blodtryck; Body Weight; Kroppsvikt; Drug Utilization; Läkemedelsförsörjning; Gastrointestinal Diseases; Mag-tarmsjukdomar; Migraine Disorders; Migränsjukdomar; Oral Health; Munhälsa; Depression; Depression; Interpersonal Relations; Mellanmänskliga relationer; Mental Health; Psykisk hälsa; Registries; Register; Smoking; Rökning; Disease; Sjukdom; Pain; Smärta; Tobacco, Smokeless; Rökfri tobak; Social Support; Socialt stöd; Stress, Psychological; Psykologisk stress; Vision, Ocular; Syn; Sleep; Sömn; Sleep Wake Disorders; Sömn- och vakenhetsstörningar; Fatigue; Trötthet; Occupations; Yrken; Occupational Exposure; Yrkesmässig exponering; Hypersensitivity; Överkänslighet; Feeding Behavior; Ätbeteende